2009
DOI: 10.1007/s00464-009-0729-3
|View full text |Cite
|
Sign up to set email alerts
|

The endoscopic U-stitch technique for primary button placement: an institution’s experience

Abstract: The endoscopic U-stitch technique is safe and allows for primary button placement in infants and children. Its complication rate compares favorably with other laparoscopic and open techniques described in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…This method uses transcutaneous U-stitches of nonabsorbable sutures on large needles for gastric fixation, placed under endoscopic visualization. Nixdorff et al 13 reported a 1.7% cellulitis rate and 0.9% colonic perforation rate in their retrospective review of 121 pediatric patients undergoing this procedure. In our technique the use of straight 18-gauge needles to place the lasso U-stitch reduces the risk of accidental intestinal injury from blind needle sweeps, comparable with T-fasteners.…”
Section: Discussionmentioning
confidence: 99%
“…This method uses transcutaneous U-stitches of nonabsorbable sutures on large needles for gastric fixation, placed under endoscopic visualization. Nixdorff et al 13 reported a 1.7% cellulitis rate and 0.9% colonic perforation rate in their retrospective review of 121 pediatric patients undergoing this procedure. In our technique the use of straight 18-gauge needles to place the lasso U-stitch reduces the risk of accidental intestinal injury from blind needle sweeps, comparable with T-fasteners.…”
Section: Discussionmentioning
confidence: 99%